Easy way to write a clear research problem statement using IRCA model: ideally, reality, consequences and aim - Dusim, Haidy Henry; Bagang, Tony Paridi; Yassin, Jain; Lo, Chor Wai; Korom, Alexius (Universiti Teknologi MARA, Kedah, 2023)
A research problem statement serves as the heart of a research endeavor. However,many authors, especially academicians, students, and postgraduates, frequently struggle to articulate a clear problem statement. As a result, they are not clear on the direction of their own research. The IRCA Model is suggested as a useful tool to help authors develop a clear problem statement in order to address this problem.IRCA stands for "Ideally, Reality, Consequences, and Aim," which are the four major themes. By including these four major themes, researchers can effectively write a clear problem statement.